Early‐life exposure to Tris(1, 3‐dichloroisopropyl) phosphate induces dose‐dependent suppression of sexual behavior in male rats. Issue 5 (22nd December 2017) - Kamishima, Manami; Hattori, Tatsuya; Suzuki, Go; Matsukami, Hidenori; Komine, Chiaki; Horii, Yasuyuki; Watanabe, Gen; Oti, Takumi; Sakamoto, Hirotaka; Soga, Tomoko; Parhar, Ishwar S.; Kondo, Yasuhiko; et al.
Abstract: Exposure to endocrine‐disrupting chemicals may adversely affect animals, particularly during development. Tris(1, 3‐dichloroisopropyl) phosphate (TDCIPP) is an organophosphate with anti‐androgen function in vitro that is present in indoor dust at relatively high concentrations. In male rats, androgens are necessary for the development of reproductive organs, as well as the endocrine and central nervous systems. However, we currently do not know the exact effects of TDCIPP exposure through suckling on subsequent reproductive behavior in males. Here, we show that TDCIPP exposure (25–250 mg kg –1 via oral administration over 28 consecutive days post‐birth) suppressed male sexual behavior and reduced testes size. These changes were dose‐dependent and appeared first in adults rather than in juveniles. These results demonstrate that TDCIPP exposure led to normal body growth and appearance in juveniles, but disrupted the endocrine system and physiology in adults. Therefore, assays should be performed using adult animals to ensure accuracy, and to confirm the influence of chemical substances given during early mammalian life. Abstract : Tris(1, 3‐dichloroisopropyl) phosphate (TDCIPP) is an endocrine‐disrupting chemical with anti‐androgen function, but we know little about its effects on male reproductive behaviors. Here, we show that pre‐weaning exposure to TDCIPP suppressed male sexual behavior in rats. The influence was dose‐dependent and appeared only when males reached maturity. Therefore, the extent of damage from TDCIPP exposure cannot be assessed at the juvenile stage, as normal body growth and sexual behavior still continues during this stage.